Social justice in the context of redistribution - Jan-Felix Kederer; Adelheid Klein; Daniel Kovarich; Lena Kumm (University of Freiburg, Institute for Economic Research, Department of Economic Policy and Constitutional Economic Theory, 2017)
[Introduction and Research Question ...] Before we turn to the main body, we briefly sketch the organisation of this paper: Section 2 addresses the different components of different social security systems including the allocation of income, a minimum income as well as the respective financing mechanisms. Section 3 covers the description, purposes, hypotheses and results of our experimental design. Section 4 deals with concluding remarks on the empirical procedure including a prospect for further research.
Keywords: 330